Алгоритм минимизации с использованием модификации метода эллипсоидов - Журбенко, Н.Г.; Чумаков, Б.М. (Теорія оптимальних рішень, 2005)
An ε-subgradient algorithm for minimization of a convex function in a finite-dimensional Euclidean space is proposed. The algorithm is updating of the ellipsoid method, it is based on a dimensional minimization procedure and it is somewhat monotonous. Algorithm’s efficiency evaluation for e -optimizations problem is given.